Importance of shoulder girdle and finger flexor muscle endurance in advanced male climbers - Draga, P.; Rokowski, R.; Sutor, A.; Pandurevic, D.; Michailov, M. L. (Frontiers in Sports and Active Living, 2024)
Aim: This study aimed to: (a) assess the relationships between climbing performance and finger and shoulder girdle muscle endurance; and (b) provide evidence on the validity of the specialized exercise tests used for the purpose.